Impact of the dynamic and static component of the sport practiced for electrocardiogram analysis in screening athletes - Maillot, N.; Guenancia, C.; Yameogo, N. V.; Gudjoncik, A.; Garnier, F.; Lorgis, L.; Chague, F.; Cottin, Y. (Scandinavian Journal of Medicine & Science in Sports, 2018)
To interpret the electrocardiogram (ECG) of athletes, the recommendations of the ESC and the Seattle criteria define type 1 peculiarities, those induced by training, and type 2, those not induced by training, to rule out cardiomyopathy. The specificity of the screening was improved by Sheikh who defined "Refined Criteria," which includes a group of intermediate peculiarities. The aim of our study was to investigate the influence of static and dynamic components on the prevalence of different types of abnormalities. The ECGs of 1030 athletes performed during preparticipation screening were interpreted using these three classifications. Our work revealed 62/16%, 69/13%, and 71/7% of type 1 peculiarities and type 2 abnormalities for the ESC, Seattle, and Refined Criteria algorithms, respectively(P<.001). For type 2 abnormalities, three independent factors were found for the ESC and Seattle criteria: age, Afro-Caribbean origin, and the dynamic component with, for the latter, an OR[95% CI] of 2.35[1.28-4.33] (P=.006) and 1.90[1.03-3.51] (P=.041), respectively. In contrast, only the Afro-Caribbean origin was associated with type 2 abnormalities using the Refined Criteria: OR[95% CI] 2.67[1.60-4.46] (P<.0001). The Refined Criteria classified more athletes in the type 1 category and fewer in the type 2 category compared with the ESC and Seattle algorithms. Contrary to previous studies, a high dynamic component was not associated with type 2 abnormalities when the Refined Criteria were used; only the Afro-Caribbean origin remained associated. Further research is necessary to better understand adaptations with regard to duratio